Efektivitas ROS Development Studio sebagai Simulator Pendukung Pengembangan Algoritma Platform Robotika - Effendy, Kevin Julianto; Budiyanta, Nova Eka (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2020)
This study aims to analyze robotics simulation tools that can be used to support algorithm development in the robot modelling process. There are several simulation tools for robot algorithm modelling that are popularly used by robotics developers. This study focuses on analyzing the effectiveness based on the features of the Robot Operating System Development Studio (ROSDS) and MATLAB as a development simulation platform using the comparative method. The results of this study claim that ROSDS is more effective than MATLAB in terms supporting the development of robotics simulation because ROS is used as a middleware in ROSDS that connects the communication between the program with the robot, so that makes it easier for making robotics simulation and ROSDS is easier to access than MATLAB. The trial case study of developing trajectory algorithm in the robot arm was carried out in this research to support the statement above, and it worked out well.